AN EXPERIENCE OF TRIMETAZIDINE USAGE IN COMORBIDITY - I. V. Kochetkova; T. M. Chernykh; G. M. Panyushkina (Российский кардиологический журнал)
Aim. To assess the dynamics of heart rate variability (HRV) during the therapy with trimetazidine instable angina patients comorbid with diabetes. Material and methods. Totally, 110 stable angina patients studied, of III functional class (FC), comorbid with type 2 diabetes (DM2), that is 53 with diabetic vegetative cardial neuropathy, and other 57 with no diabetes, that is with no vegetative cardial neuropathy, investigated with hardware and software complex.Results. Usage of trimetazidine instable angina patients of III FC, comorbid with DM2, makes it to improve the myocardial index to normal levels, to restore variability parameters, clinical condition of the patient, and facilitates the improvement of diabetic neuropathy.Conclusion. Usage of trimetazidine is practically worthy, making it to improve prognosis in coronary heart disease comorbid with DM2.